Presence of Staphylococcus aureus and staphylococcal enterotoxin A Production and Inactivation in Brazilian Cheese Bread - Campos, Fábio Martins; da Silva, Francine Fernandes; Teixeira, Nathalia Bibiana [UNESP]; de Lourdes Ribeiro de Souza da Cunha, Maria [UNESP]; de Oliveira, Tereza Cristina Rocha Moreira (FapUNIFESP (SciELO), 2022)
Ingesting food contaminated by pathogens and/or their toxins can cause foodborne illness. In this sense, this study investigated the occurrence of enterotoxigenic S. aureus in frozen cheese bread dough and assessed the production and thermosensitivity of SEA in artificially contaminated cheese dough. E. coli counts were determined by MPN. Confirmation of the presence of S. aureus was carried out by biochemical and molecular identification. The detection of the genes sea, seb, sec, and sed was performed using the PCR. The detection of SEA in artificially contaminated cheese dough, before and after baking at 180 ºC for 35 minutes was performed using the RPLA. All samples contaminated with E. coli had NMP<5.0×102 CFU / g. None of the isolated S. aureus strains expressed the classical enterotoxin genes sea, seb, sec, and sed. However, as there are 23 serologically distinct staphylococcal enterotoxins, we cannot rule out the possibility that strains expressed other enterotoxin-encoding genes. Laboratory tests showed the presence of SEA in cheese bread dough artificially contaminated with SEA-producing S. aureus after 8 h of incubation at 10 or 20 °C. Heat treatment at 180 °C for 35 minutes was not sufficient to inactivate SEA in artificially contaminated cheese bread previously incubated for 24 h at 10 or 20 °C. These results indicate a potential health risk to consumers of cheese bread and underscore the need for ingredient quality control and measures to prevent the multiplication of S. aureus during product manufacture and storage.
Keywords: Escherichia coli; foodborne outbreaks; nonclassical enterotoxin; PCR; RPLA; Sea